Normalized activation in the somatosensory cortex 30 years following nerve repair in children: an fMRI study - Chemnitz, Anette; Weibull, Andreas; Rosén, Birgitta; Andersson, Gert; Dahlin, Lars B.; Björkman, Anders (The European journal of neuroscience, 2015)
The clinical outcome following a peripheral nerve injury in the upper extremity is generally better in young children than in teenagers and in adults, but the mechanism behind this difference is unknown. In 28 patients with a complete median nerve injury sustained at the ages of 1–13 years (n = 13) and 14–20 years (n = 15), the cortical activation during tactile finger stimulation of the injured and healthy hands was monitored at a median time since injury of 28 years using functional magnetic resonance imaging (fMRI) at 3 Tesla. The results from the fMRI were compared with the clinical outcome and electroneurography. The cortical activation pattern following sensory stimulation of the median nerve‐innervated fingers was dependent on the patient's age at injury. Those injured at a young age (1–13 years) had an activation pattern similar to that of healthy controls. Furthermore, they showed a clinical outcome significantly superior (P = 0.001) to the outcome in subjects injured at a later age; however, electroneurographical parameters did not differ between the groups. In subjects injured at age 14–20 years, a more extended activation of the contralateral hemisphere was seen in general. Interestingly, these patients also displayed changes in the ipsilateral hemisphere where a reduced inhibition of somatosensory areas was seen. This loss of ipsilateral inhibition correlated to increasing age at injury as well as to poor recovery of sensory functions in the hand. In conclusion, cerebral changes in both brain hemispheres may explain differences in clinical outcome following a median nerve injury in childhood or adolescence. Cortical activation was assessed, using fMRI at 3T, 28 years after a median nerve injury. The cortical activation pattern was compared with clinical outcome and electroneurography. Patients injured before the age of 14 years had an activation pattern similar to healthy controls and an excellent clinical outcome. Those injured at age 14–20 years showed more extended activation of contralateral somatosensory areas, as well as loss of ipsilateral inhibition and poor clinical outcome. Electroneurographical parameters did not differ between the two age groups. Cerebral changes in both hemispheres may explain the superior clinical outcome following a median nerve injury in childhood.